Lignin self-protection room-temperature phosphorescent carbon dots and organic composite film, preparation method and application thereof

The lignin self-protected room temperature phosphorescence carbon dots and organic polymer composite functional films were prepared by solvent-thermal reaction method, which solved the problems of expensive equipment and environmental pollution in existing ammonia detection methods and achieved resource-friendly ammonia detection, with real-time Visual detection effect.

CN119193152APending Publication Date: 2024-12-27SHAANXI HESHI DAIRY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411380413.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing ammonia detection methods and equipment are expensive and complex, and the room temperature phosphorescent materials of carbon dots are mostly made of organic chemicals, which leads to resource consumption and environmental pollution, and lacks renewable alternative materials.

Method used

Using lignin as raw material, self-protected room temperature phosphorescence carbon dots are prepared by solvothermal reaction method, and composited with organic polymers into functional films to realize visual detection of ammonia.

Benefits of technology

It reduces production costs, realizes the high-value utilization of lignin, provides resource-friendly ammonia detection methods, has real-time and visual detection effects, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193152A_ABST
    Figure CN119193152A_ABST
Patent Text Reader

Abstract

The invention discloses a lignin self-protection room temperature phosphorescent carbon dot and an organic composite film, a preparation method and application thereof, and belongs to the technical field of biomass nanomaterials. Lignin, a heteroatom doping source and a reaction solvent are mixed, a solvothermal method is adopted for synthesis, a crude product is collected after the reaction is completed, and the crude product is sequentially subjected to filtration, rotary evaporation drying, water dissolution, dialysis and cold drying to obtain the lignin carbon dots with long afterglow self-protection room-temperature phosphorescence emission under ultraviolet excitation. And the composite film is compounded with an organic polymer to construct an organic composite film with ammonia gas visual responsiveness. The used reaction raw materials are environment-friendly in resource, the preparation method is simple, the cost is low, industrial production is easy to realize, the prepared lignin self-protection room-temperature phosphorescent carbon dots have ammonia gas visual response capability, and the provided organic composite film can be used for visual room-temperature phosphorescent sensing of ammonia gas and has wide application prospects. Therefore, food deterioration and industrial and domestic ammonia gas leakage can be detected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomass nanomaterials, in particular to a lignin self-protected room temperature phosphorescent carbon dot and an organic composite film thereof, a preparation method and application thereof. Background Art

[0002] Ammonia is a gas widely used and discharged in industrial production. It has a strong pungent odor, corrosiveness and toxicity. According to the standard (29 CFR 1910.1000) issued by the U.S. Occupational Safety and Health Administration (OSHA), the acceptable concentration limit of ammonia for humans is 25 × 10 -6 (no more than 8 h), when the concentration exceeds 500 × 10 -6 When ammonia is detected, it can cause lung damage or even death. Therefore, it is crucial to achieve trace detection of ammonia through reliable gas sensors. Currently, a variety of methods for detecting ammonia have been developed, such as electrochemical systems, gas chromatography-mass spectrometry, array systems, and high-performance liquid chromatography. However, they usually require expensive equipment and complex testing methods, have low visualization, and are not convenient for real-time detection, which greatly limits their application.

[0003] Optical detection has the outstanding characteristics of high sensitivity, good selectivity and simple operation, so it has great application potential for the detection of ammonia. At present, a variety of fluorescent materials represented by organic polymers have been widely used in the optical detection of synthetic ammonia. For example, patent CN104178133A constructs 1-(4'-carboxybiphenyl)-2,5-diphenylpyrrole (CP-TPP) fluorescent film for visual detection of ammonia, but this method requires the use of precious metal catalysts and is prepared under nitrogen protection conditions. The operation process is relatively complicated and costly, and it is not suitable for industrial production and application. Patent CN113106751B introduces a polymer for ammonia fluorescence detection, but the polymer composition is relatively complex, including a polymer substrate, a poly(glycidyl methacrylate) chain segment, a fluorescent group and an acidic group, and its visual detection ability has not been reported. It can be seen that organic fluorescent polymers still have shortcomings such as complex preparation, high cost and low visualization.

[0004] As a new type of carbon nanomaterial with a diameter of less than 10 nm, quasi-spherical shape and monodisperse, carbon dots have gradually become a rising star in the family of carbon nanomaterials due to their excellent water solubility, chemical inertness, low toxicity, easy functionalization and resistance to photobleaching. From the perspective of basic and application, optical properties are the most prominent characteristics of carbon dots. In recent years, thanks to the characteristics of fluorescence quenching and recovery of carbon dots, they have shown good application effects in the field of analytical detection. At present, patents for the application of carbon dots in ammonia detection have been disclosed. For example, patent CN115452894A introduces the application of ammonia detection by synthesizing carbon dots by hydrothermal carbonization of amino acids and siloxanes, but the detection method is not optical detection and does not have visual detection capabilities. Visual detection of carbon dots is inseparable from its room temperature phosphorescence performance. Room temperature phosphorescence from the long-lived triplet excited state allows appropriate time delay, successfully avoiding the interference of background fluorescence emission and scattered light from common biological matrices, improving detection accuracy, and delayed room temperature phosphorescence also provides a long enough time for visual observation. However, most of the current room temperature phosphorescent carbon dots are synthesized using organic chemicals as raw materials, which will inevitably increase resource consumption and harm the ecological environment in the long run. Therefore, it is urgent to find renewable alternatives to prepare room temperature phosphorescent carbon dots.

[0005] Lignin carbon dots have a wide range of application potentials in the field of room temperature phosphorescence as phosphorescent active sites, but lignin carbon dots need to be compounded with a rigid matrix to stabilize the triplet excited state in order to emit room temperature phosphorescence. The construction process is relatively complex and the intrinsic state luminescence mechanism is unclear. Its optical performance is still inferior to that of carbon dots synthesized with traditional chemicals as raw materials. In contrast, self-protected room temperature phosphorescence without the assistance of a matrix has strong stability, long life, high quantum efficiency, and rich luminescent colors. In particular, the luminescent properties can be directly regulated by controlling the preparation process, showing better potential in practical applications. Therefore, developing a method for constructing lignin self-protected room temperature phosphorescent carbon dots and exploring its ammonia visualization detection application has important theoretical and practical significance for the high-value utilization of lignin, the development of room temperature phosphorescent carbon dots, and the solution of ammonia pollution problems. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a lignin self-protected room temperature phosphorescent carbon dot and its organic composite film, preparation method and application. The reaction raw materials used are resource-friendly and environmentally friendly, the preparation method is simple, the cost is low, and it is easy to realize industrial production. The prepared lignin self-protected room temperature phosphorescent carbon dots have the ability to respond to ammonia visually. The functional film prepared by compounding them with organic polymers can be used for visual room temperature phosphorescence sensing of ammonia, and then can be used for detection of food spoilage and industrial and domestic ammonia leakage.

[0007] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for preparing lignin self-protected room temperature phosphorescent carbon dots, comprising: Lignin, a heteroatom dopant and a reaction solvent are mixed to obtain a mixed solution, and the mixed solution is subjected to a solvent thermal reaction; after the reaction is completed, a crude product is collected, and the crude product is filtered, rotary evaporated, dissolved in water, dialyzed and lyophilized to obtain lignin self-protected room temperature phosphorescent carbon dots.

[0008] The lignin is one or more of sodium lignin sulfonate, alkali lignin, enzymatic lignin, ground wood lignin, sulfate lignin, organic solvent lignin, and dioxane lignin; the heteroatom dopant is one or more of polyethyleneimine, boric acid, borax, ethylenediamine, acrylamide, diethylenetriamine, phosphoric acid, organosilane, and triethylamine trihydrofluoride; and the reaction solvent is one or more of deionized water, ethanol, methanol, formic acid, dioxane, tetrahydrofuran, acetonitrile, N, N-dimethylformamide, formamide, and acetone.

[0009] The addition ratio of the lignin, the heteroatom dopant and the reaction solvent is (0.05 ~ 5) g: (0.05 ~ 10) g: (5 ~ 70) mL.

[0010] The solvent thermal reaction is carried out at a temperature of 90 to 300° C. for 0.5 to 72 h.

[0011] The pore size of the filter membrane used in the filtration is 0.01 to 0.45 μm; the temperature of the rotary evaporation is 30 to 140°C; the molecular weight cutoff of the dialysis membrane used in the dialysis is 500 to 12000 Da, the dialysis time is 6 to 72 h; and the cold drying time is 6 to 72 h.

[0012] The present invention also provides lignin self-protected room temperature phosphorescent carbon dots prepared according to the above preparation method, wherein the lignin self-protected room temperature phosphorescent carbon dots have self-protected room temperature phosphorescent emission performance under ultraviolet light excitation.

[0013] The present invention also provides a lignin self-protected room temperature phosphorescent carbon dot-based organic composite film, comprising the above-mentioned lignin self-protected room temperature phosphorescent carbon dots.

[0014] The present invention also provides a method for preparing the above-mentioned lignin self-protected room temperature phosphorescent carbon dot-based organic composite film, comprising: The above-mentioned lignin self-protected room temperature phosphorescent carbon dots and an organic polymer solution are mixed in a ratio of (0.05 ~ 5) mg: 3 mL, wherein the concentration of the organic polymer solution is 2.5 ~ 50%, and a film-forming treatment is performed at 25 ~ 90 ° C to obtain a lignin self-protected room temperature phosphorescent carbon dot-based organic composite film.

[0015] The solute of the organic polymer solution is one or more of polyethylene glycol, polymethyl methacrylate, polyvinyl alcohol, polyacrylamide, carboxymethyl cellulose and polydimethylsiloxane.

[0016] The present invention also provides an application of a lignin self-protected room temperature phosphorescent carbon dot-based organic composite film in visual detection of ammonia. The lignin self-protected room temperature phosphorescent carbon dot-based organic composite film is placed in an ammonia environment with a concentration range of 0 to 2000 ppm for 0.05 to 72 hours, and then room temperature phosphorescent visual detection of ammonia is performed.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses lignin, a renewable aromatic polymer with the most abundant reserves in nature, as a raw material for preparation. It is resource-friendly and environmentally friendly, cheap and easy to obtain, effectively reducing production costs, and realizing high-value utilization of lignin. The present invention makes full use of the characteristic that lignin can be depolymerized and modified to produce more active hydroxyl groups in an organic solvent to promote molecular reaction crosslinking. A rigid cross-linked carbonized polymer structure is constructed in the carbon dots by solvent thermal carbonization to protect phosphorescent triplet excitons, thereby realizing self-protected room temperature phosphorescence emission without matrix assistance. The present invention makes full use of the characteristic that the solvent thermal carbonization reaction process is easy to control, regulates the reaction conditions, and optimizes the structural composition of the lignin self-protected room temperature phosphorescent carbon dots in real time, thereby improving the phosphorescence quantum efficiency, extending the luminescence life, and enriching the luminescent color.

[0018] The lignin self-protected room temperature phosphorescent carbon dot-based organic polymer film prepared by the present invention can be used for ammonia detection. The detection method is simple, easy to implement and has real-time and visual observation effects. It has broad application potential in monitoring food spoilage and industrial and domestic ammonia leakage. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for use in the embodiment: Figure 1 This is a flow chart of the preparation method of the lignin self-protected room temperature phosphorescent carbon dots and the organic composite film thereof of the present invention; Figure 2 This is a microscopic morphology of the lignin self-protected room temperature phosphorescent carbon dots prepared in Example 1 of the present invention; Figure 3 This is a particle size distribution diagram of the lignin self-protected room temperature phosphorescent carbon dots prepared in Example 1 of the present invention; Figure 4 The room temperature phosphorescence excitation and emission diagram of the lignin self-protected room temperature phosphorescent carbon dots prepared in Example 1 of the present invention; Figure 5 This is a room temperature phosphorescence lifetime diagram of the lignin self-protected room temperature phosphorescent carbon dots prepared in Example 1 of the present invention; Figure 6 (a), (b), (c), (d), (e) and (f) are room temperature phosphorescence images of the lignin self-protected room temperature phosphorescent carbon dots prepared in Example 2 of the present invention at 1s, 2s, 3s, 4s and 5s after ultraviolet light irradiation and the ultraviolet light is turned off, respectively; Figure 7 (a) and (b) are room temperature phosphorescence images of the lignin self-protected room temperature phosphorescent carbon dot-based organic composite film prepared in Example 2 of the present invention and raw shrimp before and after being stored together for 12 hours; Figure 8 A relationship diagram of the room temperature phosphorescence intensity under different ammonia concentrations for ammonia detection of the lignin self-protected room temperature phosphorescent carbon dot-based organic composite film prepared in Example 3 of the present invention; Fig. 9 This is a fitting diagram of the relationship between the ammonia concentration and the room temperature phosphorescence intensity of the lignin self-protected room temperature phosphorescent carbon dot-based organic composite film prepared in Example 3 of the present invention during ammonia detection; Fig.10 This is a microscopic morphology of the lignin self-protected room temperature phosphorescent carbon dots prepared in Example 4 of the present invention; Fig.11 This is a particle size distribution diagram of lignin self-protected room temperature phosphorescent carbon dots prepared in Example 4 of the present invention; Fig.12 Room temperature phosphorescence emission graphs of the lignin self-protected room temperature phosphorescent carbon dot-based organic composite film prepared in Example 4 of the present invention at different excitation wavelengths; Fig.13 This is a relationship diagram between the room temperature phosphorescence intensity and different ammonia concentrations of the lignin self-protected room temperature phosphorescent carbon dot-based organic composite film prepared in Example 4 of the present invention for ammonia detection. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with the accompanying drawings: like Figure 1 As shown, the present invention provides a method for preparing lignin self-protected room temperature phosphorescent carbon dots, comprising the following steps: The method comprises the following steps: mixing lignin, a heteroatom dopant and a reaction solvent to obtain a mixed solution; charging the mixed solution into a polytetrafluoroethylene high-pressure reactor to carry out a solvent thermal reaction; cooling the mixed solution to room temperature after the reaction is completed, collecting a crude product generated by the reaction, and sequentially filtering, rotary evaporating, dissolving in water, dialyzing and freeze-drying the crude product to obtain lignin self-protected room temperature phosphorescent carbon dots.

[0021] The present invention uses lignin, a renewable aromatic polymer with the most abundant reserves in nature, as a preparation raw material. The resource and environment are friendly, cheap and easily available, which effectively reduces the production cost and realizes the high-value utilization of lignin. The present invention makes full use of the characteristic that lignin can be depolymerized and modified to produce more active hydroxyl groups in organic solvents to promote molecular reaction cross-linking. A rigid cross-linked carbonized polymer structure is constructed in the carbon dots through a solvent thermal carbonization method to protect the phosphorescent triplet excitons, thereby realizing self-protected room temperature phosphorescence emission without the assistance of a matrix.

[0022] In some embodiments, the lignin is one or more of sodium lignin sulfonate, alkali lignin, enzymatic lignin, groundwood lignin, sulfate lignin, organic solvent lignin, and dioxane lignin. It should be noted that the selected lignin can provide a rich carbon source and has good biodegradability and renewability. It is preferably one or more of sodium lignin sulfonate, alkali lignin, enzymatic lignin, and dioxane lignin; the preferred lignin has better performance in providing a carbon source.

[0023] In some embodiments, the heteroatom dopant is one or more of polyethyleneimine, boric acid, borax, ethylenediamine, acrylamide, diethylenetriamine, phosphoric acid, organosilane, triethylamine trihydrofluoride. It should be noted that the selected heteroatom dopant can change the structure of the carbon dots and improve the efficiency and life of the phosphorescent carbon dots. It is preferably one or more of diethylenetriamine, phosphoric acid, organosilane, triethylamine trihydrofluoride, and boric acid. The present invention has no special limitation on the source of the heteroatom dopant used, and commercially available products known to those skilled in the art can be used, preferably anhydrous heteroatom dopant.

[0024] In some embodiments, the reaction solvent is one or more of deionized water, ethanol, methanol, formic acid, dioxane, tetrahydrofuran, acetonitrile, N, N-dimethylformamide, formamide, and acetone. It should be noted that selecting a suitable solvent can provide a better reaction environment, improve reaction efficiency, and obtain high-quality phosphorescent carbon dots. Preferably, it is one or more of deionized water, ethanol, methanol, dioxane, acetonitrile, N, N-dimethylformamide, and acetone. The present invention has no particular limitation on the source of the organic solvent used, and commercially available products known to those skilled in the art can be used, preferably analytically pure organic solvents.

[0025] The present invention has no particular limitation on the mixing order of lignin, heteroatom dopant and reaction solvent. Preferably, the reaction solvent is added to the mixture of lignin and heteroatom dopant, and more preferably, lignin, heteroatom dopant and organic solvent are added in sequence.

[0026] The present invention has no special restrictions on the mixing method of the lignin, heteroatom dopant and reaction solvent, and a mixing method well known to those skilled in the art can be used. The present invention preferably uses stirring, and more preferably ultrasonic mixing. The present invention has no special restrictions on the frequency, time and temperature of the ultrasonic mixing, as long as the materials can be mixed evenly.

[0027] In some embodiments, the ratio of the lignin, the heteroatom dopant and the reaction solvent is preferably (0.05 ~5) g: (0.05 ~ 10) g: (5 ~ 70) mL; more preferably (0.1 ~ 4) g: (0.1 ~ 8) g: (10 ~ 50) mL, and most preferably (0.2 ~ 3) g: (0.5 ~ 6) g: (20 ~ 40) mL. It should be noted that the amount of lignin added as a carbon source directly affects the yield and quality of the product. Too low a lignin content leads to incomplete reaction and low product yield, while too high a lignin content may affect the uniformity of the reaction and even lead to agglomeration. An appropriate amount of heteroatom dopant can significantly improve the efficiency and lifetime of the room temperature phosphorescent carbon dots, but too much doping may introduce too many defect states, leading to increased non-radiative recombination and reduced performance of the room temperature phosphorescent carbon dots. An appropriate amount of reaction solvent can ensure that the raw materials are fully dissolved and the reaction proceeds uniformly, but too much reaction solvent will increase the volume and energy consumption of the reaction system and even affect the concentration and performance of the product. Further narrowing the ratio range of each component can prepare lignin self-protected room temperature phosphorescent carbon dots with excellent phosphorescent properties and high stability.

[0028] In some embodiments, the solvent thermal reaction temperature is preferably 90 ~ 300 ° C, more preferably 120 ~ 260 ° C, and most preferably 160 ~ 230 ° C; the solvent thermal reaction time is preferably 0.5 ~ 72 h, more preferably 1 ~ 48 h, and most preferably 2 ~ 24 h. It should be noted that when the reaction temperature is lower than 90 ° C, the reaction rate may be too slow, resulting in low product yield or incomplete structure; while when it is higher than 300 ° C, it may cause excessive carbonization or side reactions, affecting the room temperature phosphorescence performance and stability of the product. The appropriate reaction time ensures that the lignin is completely depolymerized and cross-linked into a carbonized polymer with a rigid structure. Too short a reaction time may lead to incomplete reaction and poor product performance; while too long a reaction time may increase energy consumption and cost, and even cause unnecessary side reactions. The preferred reaction temperature and time range enable the product to achieve the best in terms of room temperature phosphorescence emission efficiency, stability and yield.

[0029] In some embodiments, the pore size of the filtration membrane is preferably 0.01 to 0.45 μm, more preferably 0.22 to 0.45 μm, and most preferably 0.22 μm.

[0030] In some embodiments, the rotary evaporation temperature is preferably 30 to 140°C, more preferably 50 to 120°C, and most preferably 70 to 100°C; the present invention has no particular limitation on the rotary evaporation time, as long as it can achieve complete drying. It should be noted that a suitable rotary evaporation temperature can ensure the evaporation rate and avoid damaging the structure of the product.

[0031] In some embodiments, the molecular weight cutoff of the dialysis membrane is 500 to 12000 Da, more preferably 500 to 3500 Da, and most preferably 1000 Da; the dialysis time is preferably 6 to 72 h, more preferably 12 to 48 h, and most preferably 24 h.

[0032] In some embodiments, the cold drying time of the lignin self-protected room temperature phosphorescent carbon dots is preferably 6 to 72 h, more preferably 12 to 56 h, and most preferably 48 h.

[0033] The present invention makes full use of the easy-to-control feature of the solvent thermal carbonization reaction process, regulates the reaction conditions, and optimizes the structural composition of the lignin self-protected room temperature phosphorescent carbon dots in real time, thereby improving the phosphorescence quantum efficiency, extending the luminescence lifetime, and enriching the luminescent color.

[0034] The invention also discloses lignin self-protected room temperature phosphorescent carbon dots prepared by the preparation method, which have self-protected room temperature phosphorescent emission performance under ultraviolet light excitation.

[0035] The present invention also discloses a lignin self-protected room temperature phosphorescent carbon dot-based organic composite film, which is prepared based on the above-mentioned lignin self-protected room temperature phosphorescent carbon dots.

[0036] like Figure 1 As shown, the present invention also provides a method for preparing the above-mentioned lignin self-protected room temperature phosphorescent carbon dot-based organic composite film, the specific steps are: The lignin self-protected room temperature phosphorescent carbon dots prepared by the preparation method are mixed with an organic polymer solution and then subjected to film-forming treatment to prepare a lignin self-protected room temperature phosphorescent carbon dots-based organic composite film.

[0037] The organic composite film constructed by the present invention by combining the prepared carbon dots with organic polymers has good ammonia responsiveness, shows good application effect in real-time and visual detection of ammonia, and has broad application potential in monitoring food spoilage and industrial and domestic ammonia leakage.

[0038] In some embodiments, the ratio of lignin self-protected room temperature phosphorescent carbon dots to organic polymer solution is (0.05~5) mg: 3 mL, and the concentration of the organic polymer solution is 2.5~50%. It should be noted that the control of the amount of room temperature phosphorescent carbon dots and organic polymer solution can ensure the uniform distribution of room temperature phosphorescent carbon dots on the organic polymer film, and ensure the range and accuracy of detection.

[0039] In some embodiments, the film forming process is performed at a temperature of 25 to 90°C.

[0040] In some embodiments, the solute of the organic polymer solution is one or more of polyethylene glycol, polymethyl methacrylate, polyvinyl alcohol, polyacrylamide, carboxymethyl cellulose, and polydimethylsiloxane.

[0041] The present invention also provides an application of a lignin self-protected room temperature phosphorescent carbon dot-based organic composite film in visual detection of ammonia. The lignin self-protected room temperature phosphorescent carbon dot-based organic composite film is placed in an ammonia environment with a concentration range of 0 to 2000 ppm. After 0.5 to 72 hours, the self-protected room temperature phosphorescence intensity of the lignin carbon dots is detected using a fluorescence spectrophotometer to conduct a room temperature phosphorescence visual detection experiment of ammonia.

[0042] The following is a detailed description of the preparation method of the lignin self-protected room temperature phosphorescent carbon dots provided by the present invention and the application effect of the organic composite film in the visual detection of ammonia gas in conjunction with the examples, but they should not be understood as limiting the scope of protection of the present invention.

[0043] Example 1 Weigh 0.5 g of alkali lignin and 5 g of boric acid, add 30 mL of deionized water / ethanol mixed solvent, and mix ultrasonically for 10 min. The obtained reaction mixture was added to a 100 mL polytetrafluoroethylene high-pressure reactor, and the reactor was subjected to solvent thermal treatment at 220 °C for 6 h in a homogeneous reactor, and then heated to 220 °C at room temperature at a heating rate of 5 °C / min. After the reaction was completed, the reactor was naturally cooled to room temperature, and the crude product was filtered with a filter membrane with a pore size of 0.22 μm, dried by rotary evaporation at 60 °C, and then dissolved in water, dialyzed with a dialysis membrane with a molecular weight cutoff of 1000 Da for 48 h, and lyophilized to obtain lignin self-protected room temperature phosphorescent carbon dots.

[0044] After testing, such as Figure 2 As shown in Figure 2, the lignin self-protected room temperature phosphorescent carbon dots have a quasi-spherical, monodisperse structure with a lattice spacing of 0.206 nm. Figure 3 As shown, the average size is 7.76 ± 0.12 nm, and the particle size distribution ranges from 3.61 to 13.27 nm; Figure 4As shown, under 454 nm excitation, the room temperature phosphorescence emission peak appears at 540 nm; Figure 5 As shown, the room temperature phosphorescence lifetime is calculated to be 367.26 ms.

[0045] Example 2 Weigh 0.1 g of enzymatic lignin, 2 g of phosphoric acid and 1 g of ethylenediamine, add 20 mL of deionized water, and mix ultrasonically for 10 min. The obtained reaction mixture was added to a 100 mL polytetrafluoroethylene autoclave, and the autoclave was solvothermally treated at 260 °C for 6 h in a homogeneous reactor, and then heated to 260 °C at room temperature at a heating rate of 5 °C / min. After the reaction was completed, the autoclave was naturally cooled to room temperature, and the crude product was filtered with a filter membrane with a pore size of 0.22 μm, dried by rotary evaporation at 60 °C, and then dissolved in water, dialyzed with a dialysis membrane with a molecular weight cutoff of 500 Da for 24 h, and lyophilized to obtain lignin self-protected room temperature phosphorescent carbon dots.

[0046] 1 mL of 10 mg / mL lignin self-protected room temperature phosphorescent carbon dots aqueous solution was mixed with 3 mL of 5% polyvinyl alcohol and then the mixture was heated at 60 °C to synthesize a lignin self-protected room temperature phosphorescent carbon dots-based organic composite film.

[0047] After testing, such as Figure 6 As shown in the figure, the lignin self-protected room temperature phosphorescent carbon dots emit blue-white fluorescence under 365 nm ultraviolet light. After the ultraviolet light source is turned off, a green afterglow is observed, and the light can continue to glow for 5 s. When ammonia is present, the room temperature phosphorescent color of the organic composite film changes from dark green to bright green under 365 nm ultraviolet light excitation; Figure 7 As shown, after being stored with raw shrimp for 12 h, the room temperature phosphorescence color of the film also changed from dark green to bright green.

[0048] Example 3 Weigh 1 g of sodium lignin sulfonate and 0.5 g of triethylamine trihydrofluoride, add 25 mL of acetonitrile / N, N-dimethylformamide mixed solvent, and mix by ultrasonic for 10 min. Add the obtained reaction mixture into a 100 mL polytetrafluoroethylene autoclave, and heat the autoclave at 200 °C for 12 h in a homogeneous reactor, and heat it to 200 °C at room temperature at a heating rate of 5 °C / min. After the reaction is completed, the autoclave is cooled to room temperature naturally, and the crude product is filtered with a filter membrane with a pore size of 0.22 μm, dried by rotary evaporation at 60 °C, and then dissolved in water, and dialyzed with a dialysis membrane with a molecular weight cutoff of 500 Da for 24 h. After being lyophilized, lignin self-protected room temperature phosphorescent carbon dots are obtained.

[0049] 1 mL of 3 mg / mL lignin self-protected room temperature phosphorescent carbon dots aqueous solution was mixed with 3 mL of 10% carboxymethyl cellulose and then the mixture was heated at 70 °C to synthesize the lignin self-protected room temperature phosphorescent carbon dots-based organic composite film.

[0050] After testing, the lignin self-protected room temperature phosphorescent carbon dots emit bright blue fluorescence under 365 nm ultraviolet light, and emit green room temperature phosphorescence after turning off the ultraviolet light. The organic composite film can be used for ammonia detection, such as Figure 8 As shown in Figure 2, the room temperature phosphorescence intensity increases with the increase of ammonia concentration, as shown in Figure 2 Fig. 9 As shown in the figure, the minimum detection limit reaches 0.17 ppm and the linear detection range is 0 ~ 130 ppm.

[0051] Example 4 Weigh 0.05 g of organic solvent lignin and 0.05 g of organosilane, add 8 mL of acetone solvent, and mix ultrasonically for 10 min. The obtained reaction mixture was added to a 20 mL polytetrafluoroethylene high-pressure reactor, and the reactor was subjected to solvent thermal treatment at 150 °C for 12 h in a homogeneous reactor, and then heated to 150 °C at room temperature at a heating rate of 5 °C / min. After the reaction was completed, the reactor was naturally cooled to room temperature, and the crude product was filtered with a filter membrane with a pore size of 0.22 μm, dried by rotary evaporation at 40 °C, and then dissolved in water, and dialyzed with a dialysis membrane with a molecular weight cutoff of 500 Da for 72 h. After being lyophilized, lignin self-protected room temperature phosphorescent carbon dots were obtained.

[0052] 1 mL of 0.05 mg / mL lignin self-protected room temperature phosphorescent carbon dots aqueous solution was mixed with 1 mL of 2.5% polymethyl methacrylate and then the mixture was heated to 80 °C to synthesize the lignin self-protected room temperature phosphorescent carbon dots-based organic composite film.

[0053] After testing, such as Fig.10 As shown in Figure 2, the lignin self-protected room temperature phosphorescent carbon dots have a quasi-spherical, monodisperse structure with a lattice spacing of 0.217 nm. Fig.11 As shown in the figure, the average size is 9.98 ± 0.11 nm, and the particle size distribution ranges from 5.80 to 14.29 nm. Fig.12 As shown in , the carbon dot-based organic composite film exhibits room temperature phosphorescence emission behavior dependent on the excitation wavelength under 300 ~ 460 nm excitation wavelength, and the optimal emission peak is 517 nm; Fig.13 As shown in the figure, within the range of ammonia concentration of 0 ~1200 ppm, the room temperature phosphorescence intensity of the film gradually increases with the increase of ammonia concentration.

[0054] Example 5 Weigh 3 g of organic solvent lignin and 6 g of polyethyleneimine, add 20 mL of tetrahydrofuran, and mix ultrasonically for 10 min. Add the obtained reaction mixture into a 100 mL polytetrafluoroethylene autoclave, and heat the autoclave at 230 °C for 12 h in a homogeneous reactor, and heat it to 230 °C at room temperature at a heating rate of 5 °C / min. After the reaction is completed, the autoclave is naturally cooled to room temperature, and the crude product is filtered with a filter membrane with a pore size of 0.22 μm, dried by rotary evaporation at 70 °C, and then dissolved in water, and dialyzed with a dialysis membrane with a molecular weight cutoff of 1000 Da for 24 h. After being lyophilized, lignin self-protected room temperature phosphorescent carbon dots are obtained.

[0055] 1 mL of 3 mg / mL lignin self-protected room temperature phosphorescent carbon dots aqueous solution was mixed with 3 mL of 25% polyethylene glycol and then the mixture was heated at 60 °C to synthesize the lignin self-protected room temperature phosphorescent carbon dots-based organic composite film.

[0056] Example 6 Weigh 1 g of sodium lignin sulfonate and 2 g of polyethyleneimine, add 30 mL of acetonitrile / N, N-dimethylformamide mixed solvent, and mix by ultrasonic for 10 min. Add the obtained reaction mixture into a 100 mL polytetrafluoroethylene autoclave, and heat the autoclave at 160 °C for 12 h in a homogeneous reactor, and heat it to 160 °C at room temperature at a heating rate of 5 °C / min. After the reaction is completed, the autoclave is naturally cooled to room temperature, and the crude product is filtered with a filter membrane with a pore size of 0.22 μm, dried by rotary evaporation at 100 °C, and then dissolved in water, and dialyzed with a dialysis membrane with a molecular weight cutoff of 1000 Da for 24 h. After being lyophilized, lignin self-protected room temperature phosphorescent carbon dots are obtained.

[0057] 1 mL of 3 mg / mL lignin self-protected room temperature phosphorescent carbon dots aqueous solution was mixed with 3 mL of 10% polyvinyl alcohol to form a lignin self-protected room temperature phosphorescent carbon dots-based organic composite film.

[0058] The lignin in the above embodiments can also be replaced by ground wood lignin, sulfate lignin or dioxane lignin, which has the same or similar effects as the lignin used in Examples 1-6.

[0059] The heteroatom dopant in the above embodiments may also be replaced by borax, acrylamide, organosilane or triethylamine trihydrofluoride, which has the same or similar effect as the heteroatom dopant used in embodiments 1-6.

[0060] The reaction solvents in the above embodiments can also be replaced by ethanol, methanol, formic acid, dioxane, formamide, acetone, and sulfuric acid of different concentrations, which have the same or similar effects as the reaction solvents used in Examples 1-6.

[0061] The solute of the organic polymer solution in the above embodiment can also be replaced by polymethyl methacrylate, polyacrylamide, or polydimethylsiloxane, which has the same or similar effect as the organic polymer solution used in embodiments 2 to 6.

[0062] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art can still modify or make equivalent substitutions to the specific implementations of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention are within the scope of protection of the claims of the present invention to be approved.

Claims

1. A method for preparing lignin self-protected room temperature phosphorescent carbon dots, characterized in that: include: Mixing lignin, a heteroatom dopant and a reaction solvent to obtain a mixed solution, and subjecting the mixed solution to a solvothermal reaction; After the reaction is completed, the crude product is collected, filtered, rotary evaporated, dissolved in water, dialyzed and freeze-dried to obtain lignin self-protected room temperature phosphorescent carbon dots.

2. The method for preparing lignin self-protected room temperature phosphorescent carbon dots according to claim 1, characterized in that: The lignin is one or more of sodium lignin sulfonate, alkali lignin, enzymatic lignin, ground wood lignin, sulfate lignin, organic solvent lignin, and dioxane lignin; the heteroatom dopant is one or more of polyethyleneimine, boric acid, borax, ethylenediamine, acrylamide, diethylenetriamine, phosphoric acid, organosilane, and triethylamine trihydrofluoride; and the reaction solvent is one or more of deionized water, ethanol, methanol, formic acid, dioxane, tetrahydrofuran, acetonitrile, N, N-dimethylformamide, formamide, and acetone.

3. The method for preparing lignin self-protected room temperature phosphorescent carbon dots according to claim 1, characterized in that: The addition ratio of the lignin, the heteroatom dopant and the reaction solvent is (0.05 ~ 5) g: (0.05 ~ 10) g: (5 ~ 70) mL.

4. The method for preparing lignin self-protected room temperature phosphorescent carbon dots according to claim 1, characterized in that: The solvent thermal reaction is carried out at a temperature of 90 to 300° C. for 0.5 to 72 h.

5. The method for preparing lignin self-protected room temperature phosphorescent carbon dots according to claim 1, characterized in that: The pore size of the filter membrane used in the filtration is 0.01 to 0.45 μm; the temperature of the rotary evaporation is 30 to 140°C; the molecular weight cutoff of the dialysis membrane used in the dialysis is 500 to 12000 Da, the dialysis time is 6 to 72 h; and the cold drying time is 6 to 72 h.

6. The lignin self-protected room temperature phosphorescent carbon dots prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The lignin self-protected room temperature phosphorescent carbon dots have self-protected room temperature phosphorescent emission performance under ultraviolet light excitation.

7. A lignin self-protected room temperature phosphorescent carbon dot-based organic composite film, characterized in that: It includes the lignin self-protected room temperature phosphorescent carbon dots as described in claim 6.

8. The method for preparing the lignin self-protected room temperature phosphorescent carbon dot-based organic composite film according to claim 7, characterized in that: include: The lignin self-protected room temperature phosphorescent carbon dots described in claim 6 and an organic polymer solution are mixed in a ratio of (0.05 ~ 5) mg:3 mL, wherein the concentration of the organic polymer solution is 2.5 ~ 50%, and a film-forming treatment is performed at 25 ~ 90 ° C to obtain a lignin self-protected room temperature phosphorescent carbon dot-based organic composite film.

9. The method for preparing the lignin self-protected room temperature phosphorescent carbon dot-based organic composite film according to claim 8, characterized in that: The solute of the organic polymer solution is one or more of polyethylene glycol, polymethyl methacrylate, polyvinyl alcohol, polyacrylamide, carboxymethyl cellulose and polydimethylsiloxane.

10. The use of the lignin self-protected room temperature phosphorescent carbon dot-based organic composite film according to claim 7 in visual detection of ammonia gas, characterized in that: The lignin self-protected room temperature phosphorescent carbon dot-based organic composite film is placed in an ammonia environment with a concentration range of 0 to 2000 ppm for 0.05 to 72 hours, and then room temperature phosphorescence visualization detection of ammonia is performed.